2016
DOI: 10.1080/10428194.2016.1198959
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and motivating factors for treatment-free remission in chronic myeloid leukemia

Abstract: With BCR-ABL1 tyrosine kinase inhibitors (TKIs), such as imatinib, nilotinib, dasatinib, bosutinib, and ponatinib, many patients with chronic myeloid leukemia in chronic phase (CML-CP) can expect to live near-normal life spans. Current treatment recommendations of the National Comprehensive Cancer Network and the European LeukemiaNet state that patients with CML-CP should remain on TKI therapy indefinitely. However, there is increasing evidence from clinical trials that some patients with sustained deep molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Normalization of many immune cell populations early in the setting of TFR and MolR, at least by 3 months following the initial timepoint of TKI cessation, may be linked to the dynamic nature of the immune system as evidenced by its constant immune surveillance and the enhanced net effector immune responses and decreased PD-1 and immune suppressors observed in CML patients in DMR compared to diagnosis (12). Thus, longer follow-up of patients in all TFR studies is critically needed to determine how long patients will ultimately be able to maintain TFR (148). In this regard, immune monitoring may reveal an optimum threshold level of immune effector responses in which TKI cessation is more achievable and successful, which could prove especially informative for patients contemplating a second TKI discontinuation attempt following initial failure.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Normalization of many immune cell populations early in the setting of TFR and MolR, at least by 3 months following the initial timepoint of TKI cessation, may be linked to the dynamic nature of the immune system as evidenced by its constant immune surveillance and the enhanced net effector immune responses and decreased PD-1 and immune suppressors observed in CML patients in DMR compared to diagnosis (12). Thus, longer follow-up of patients in all TFR studies is critically needed to determine how long patients will ultimately be able to maintain TFR (148). In this regard, immune monitoring may reveal an optimum threshold level of immune effector responses in which TKI cessation is more achievable and successful, which could prove especially informative for patients contemplating a second TKI discontinuation attempt following initial failure.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Accordingly, treatment-free remission (TFR) has become a treatment goal for many patients with CML-CP in DMR. Typically, TFR is attempted in selected patients in the context of DMR, as measured by a reduction in BCR-ABL1 transcript levels on the International Scale (IS), ranging from 0.01% (MR 4 ) to 0.0032% (MR 4.5 ) to 0.001% (MR 5 ) [26]. Successful TFR has been demonstrated in several clinical trials, the majority of which have included patients discontinuing long-term imatinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies thereafter confirmed that approximately 50% of patients with CML who have sustained DMR remained in TFR ≥1 year after stopping treatment 9‐14 . The duration of exposure to TKI and DMR duration before TKI discontinuation are considered the most relevant prognostic factors for the success of TKI cessation 15 . Consequently, the traditional recommendation for lifelong TKI therapy was recently dropped for patients with CML, and TKI cessation guidelines have been issued by international experts 16,17 …”
Section: Introductionmentioning
confidence: 99%